2011
DOI: 10.1245/s10434-011-1775-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Relevant Biomarkers to Select Patients for Targeted Inhibitor Therapy after Resection of Hepatocellular Carcinoma

Abstract: High expression of PDGFR-α and PDGFR-β may be independently associated with decreased OS irrespective of margin status, MELD score, and tumor extent. This finding may help to select patients who would benefit from targeted inhibitor therapy in the adjuvant setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 22 publications
4
20
0
Order By: Relevance
“…In accordance with other previous studies [14, 17, 18], our study also demonstrated that strong PDGFRα expression in tumor sites was associated with poor survival outcome after HCC resection. However, the expression of PDGFRα did not necessarily associated with underlying liver fibrosis/cirrhosis or the expression of PDGFRα in adjacent non-tumor site of the liver.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with other previous studies [14, 17, 18], our study also demonstrated that strong PDGFRα expression in tumor sites was associated with poor survival outcome after HCC resection. However, the expression of PDGFRα did not necessarily associated with underlying liver fibrosis/cirrhosis or the expression of PDGFRα in adjacent non-tumor site of the liver.…”
Section: Discussionsupporting
confidence: 93%
“…In breast and prostate cancer, stromal PDGFRb expression correlates with shorter survival (6,7). Increased expression of PDGFRb is also associated with poor overall survival in angiosarcoma (8), hepatocellular carcinoma (9), and a subset of non-small cell lung cancers (10).…”
mentioning
confidence: 99%
“…Some key mediators of these pathways include the following: VEGFR, Raf, and PDGFR. These proteins have increasingly become important for the treatment of HCC because they are targeted by multikinase inhibitors [25]. Sorafenib is a multiple kinase inhibitor that specifically acts on VEGFR 2-3, PDGFR-β and Raf kinases (Raf-1) and prolongs survival time in patients with advanced HCC [12].…”
Section: Discussionmentioning
confidence: 99%